2022
DOI: 10.3390/jcm11102713
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Emptive Analgesia on the Postoperative Pain in Pediatric Otolaryngology: A Randomized, Controlled Trial

Abstract: The aim of this randomized, controlled trial was to determine whether children undergoing otolaryngological procedures (adenoidectomy, adenotonsillotomy, or tonsillectomy) benefit from pre-emptive analgesia in the postoperative period. Methods: Fifty-five children were assessed for eligibility for the research. Four children refused to participate during the first stage of the study, leaving fifty-one (n = 51) to be randomly assigned either to receive pre-emptive analgesic acetaminophen (15 mg/kg; n = 26) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…New developments in ENT surgeries include pre-emptive analgesia, non-opioid analgesics, and nerve stimulation therapy. A randomized controlled trial demonstrated that pre-emptive analgesia using nalbuphine and dexamethasone effectively decreased postoperative pain in pediatric otolaryngology patients [ 36 ]. Non-opioid analgesics, like NSAIDs, have exhibited the capacity to reduce postoperative vomiting and manage pain comparably to opioids [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…New developments in ENT surgeries include pre-emptive analgesia, non-opioid analgesics, and nerve stimulation therapy. A randomized controlled trial demonstrated that pre-emptive analgesia using nalbuphine and dexamethasone effectively decreased postoperative pain in pediatric otolaryngology patients [ 36 ]. Non-opioid analgesics, like NSAIDs, have exhibited the capacity to reduce postoperative vomiting and manage pain comparably to opioids [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…A randomized controlled trial demonstrated that pre-emptive analgesia using nalbuphine and dexamethasone effectively decreased postoperative pain in pediatric otolaryngology patients [ 36 ]. Non-opioid analgesics, like NSAIDs, have exhibited the capacity to reduce postoperative vomiting and manage pain comparably to opioids [ 36 ]. Hypoglossal nerve stimulation therapy, also recognized as upper airway stimulation, emerges as a promising treatment for obstructive sleep apnea [ 37 ].…”
Section: Reviewmentioning
confidence: 99%